THE EFFECT OF THE SKYPE TM CONFERENCE CALL ON ENGLISH SPEAKING ANXIETY - Nermin Punar; Levent Uzun (Informascope, 2019)
As a result of the globalized world, technology has become the center of our lives and changes a lot of things such as our education and communication.  Educational institutions have started to use some online communication platforms such as Skype TM while teaching a second language. This research examines the effect of Skype TM on foreign language learners' speaking anxiety levels and tries to find out the differences in foreign language speaking anxiety levels between the traditional speaking lesson and the Skype TM Conference Call lesson. Twenty-one B1-B2 level adult English language learners participated in this study and a true experimental research design was used. The data were analyzed by paired samples t-test analysis of pre- and post-tests of participants. The results indicated that Skype TM had an impact on foreign language learners' speaking anxiety because it reduced the anxiety levels of learners in the experimental group.